Congenital Heart Defects in the United States: Estimating the Magnitude of the Affected Population in 2010 - Gilboa, Suzanne M; Devine, Owen J; Kucik, James E; Oster, Matthew E; Riehle-Colarusso, Tiffany; Nembhard, Wendy N; Xu, Ping; Correa, Adolfo; Jenkins, Kathy; Marelli, Ariane J (Circulation (New York, N.Y.), 2016)
Because of advancements in care, there has been a decline in mortality from congenital heart defects (CHDs) over the past several decades. However, there are no current empirical data documenting the number of people living with CHDs in the United States. Our aim was to estimate the CHD prevalence across all age groups in the United States in the year 2010. The age-, sex-, and severity-specific observed prevalence of CHDs in Québec, Canada, in the year 2010 was assumed to equal the CHD prevalence in the non-Hispanic white population in the United States in 2010. A race-ethnicity adjustment factor, reflecting differential survival between racial-ethnic groups through 5 years of age for individuals with a CHD and that in the general US population, was applied to the estimated non-Hispanic white rates to derive CHD prevalence estimates among US non-Hispanic blacks and Hispanics. Confidence intervals for the estimated CHD prevalence rates and case counts were derived from a combination of Taylor series approximations and Monte Carlo simulation. We estimated that ≈2.4 million people (1.4 million adults, 1 million children) were living with CHDs in the United States in 2010. Nearly 300 000 of these individuals had severe CHDs. Our estimates highlight the need for 2 important efforts: planning for health services delivery to meet the needs of the growing population of adults with CHD and the development of surveillance data across the life span to provide empirical estimates of the prevalence of CHD across all age groups in the United States.